Workplace Violence against Health Care Providers in Emergency Departments: an Underrated Problem - Ali Talib Hameed1 , Amer Abdullah Sachit2, Hussein Abdulmohsin Dabis3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Staff employed in emergency departments (EDs) in the hospitals are excessively prone toworkplace violence (WPV) in comparison to individuals working in other departments. Such thing lead toslight or serious injuries to these employees. In addition, it may cause physical injury and disability, lowperformance at job, and finally an uncomfortable working setting for the staff.Materials and methods: A descriptive study was applied to assess the prevalence of WPV and relatedfactors. This study was conducted at the EDs of four teaching hospitals in Al-Nasiriyah city. Study samplewas drawn from emergency physicians, nurses, pharmacists, and laboratory technicians. Both genders staffswere included.Results: The results involved answers from 426 employee in the emergency department. The most reportedform of violence in the staff in the past year in this research was emotional violence, which is reported by78.5% of the sample, then physical abuse (14.3%) and sexual abuse at last (5.2%).Conclusion: This study exhibited many findings on a group of WPV cases, in addition to the features andissues related to exposure to violence. The findings undoubtedly prove the priority of considering this issuein Iraqi hospitals and the importance to develop urgent and appropriate interventions.